Book review: John Mwangi Githigaro, Countering Violent Extremism in Kenya: Community, State, and Security Perspectives (London: Lexington Books, 2024, 131pp) - Schneider, Richárd (Journal of Central and Eastern European African Studies, 2025)
No abstract is provided.